2016
DOI: 10.1155/2016/7654321
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Induction of Definitive and Pancreatic Endoderm Cell Fate in Human Fibroblasts

Abstract: Reprogramming can occur by the introduction of key transcription factors (TFs) as well as by epigenetic changes. We demonstrated that histone deacetylase inhibitor (HDACi) Trichostatin A (TSA) combined with a chromatin remodeling medium (CRM) induced expression of a number of definitive endoderm and early and late pancreatic marker genes. When CRM was omitted, endoderm/pancreatic marker genes were not induced. Furthermore, treatment with DNA methyltransferase inhibitor (DNMTi) 5-azacytidine (5AZA) CRM did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Before lysis, cells were observed by phase-contrast microscopy, and we noticed that cells treated with TSA, in contrast to AZA treated cells, acquired an elongated morphology (Figure 4A left). The analysis of pluripotency markers such as Oct4 and Nanog [23,24] and differentiation markers such as Nkx6.1 and Pdx1 [25] are in line with the epigenetic pattern of regulation of these genes suggesting the priming of a differentiation program (Figure 4A right).…”
Section: Dna Methylation and Chromatin Acetylation Affect Ink4a And Arf Gene Expression In Escssupporting
confidence: 69%
“…Before lysis, cells were observed by phase-contrast microscopy, and we noticed that cells treated with TSA, in contrast to AZA treated cells, acquired an elongated morphology (Figure 4A left). The analysis of pluripotency markers such as Oct4 and Nanog [23,24] and differentiation markers such as Nkx6.1 and Pdx1 [25] are in line with the epigenetic pattern of regulation of these genes suggesting the priming of a differentiation program (Figure 4A right).…”
Section: Dna Methylation and Chromatin Acetylation Affect Ink4a And Arf Gene Expression In Escssupporting
confidence: 69%
“…Inhibition of histone deacetylases drives cells toward differentiation by regulating the expression of differentiation- and pluripotency-associated genes. Many studies demonstrated that TSA enhances cell differentiation [ 4 , 5 , 6 ] by negatively regulating the expression of stemness markers [ 7 ], such as Oct4 [ 8 ], and simultaneously activating differentiation markers, such as Pdx1 [ 9 ]. The molecular mechanism of TSA-mediated regulation of gene activation and repression is very likely related to post-translational modifications of histones.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA was used as a cell scaffold to construct the artificial islet tissues, and fibroblasts were used to modify the PLGA membrane to improve the biocompatibility with pancreatic stem cells. Based on related studies on the induction of the differentiation of pancreatic stem cells, [21][22][23][24][25] we used the two-step induction method to induce pancreatic stem cells to differentiate into insulin-producing cells. We constructed a biomodified PLGA membrane, which was a composite cultured with pancreatic stem cells, forming an artificial islet tissue.…”
Section: Introductionmentioning
confidence: 99%